East African Community (EAC) uses aflatoxin technical papers to prepare aflatoxin policy briefs that are endorsed by the Council of Ministers of the EAC. - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
For the East African Community (EAC), IITA prepared 11 Technical Papers (TPs) on key sectoral issues impacted by aflatoxins. All available evidence of each sector was comprehensively reviewed, and action plans recommended to manage the impacts. Establishment and sharing of this knowledge base laid the foundation for policies to address the aflatoxin-related food safety issues. The TPs guided the EAC secretariat to prepare nine policy briefs that were endorsed by the EAC Council of Ministers and publicly released.